THE EFFECT OF PSYCHOLOGICAL STRESS ON MPF INTRAFOLLICULAR - NOVIKA, REVI G. H.; SANTOSO, BUDI; WIDJIATI, WIDJIATI (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the study is to investigate the influence of cortisol and Heat Shock Protein 70 (HSP70) on the stressed mice to maturation promoting factor (MPF) expression intrafollicular. Methods: Experimental laboratory with Randomized Post Test Only Control Group Design was carried out on intrafollicular mice. Divided into two groups, experimental and control groups. The experimental group was given a 95 dB 4 hours/day noisy exposure for 5 days which was analogous to psychological stress in humans and the control group was not given noisy exposure. Furthermore, both groups were examined for cortisol levels to ensure stress in mice. Heat shock protein 70 (HSP70) expression was examined as the main regulatory protein for stress response and Maturation promoting factor (MPF) expression which is a mediator for oocyte maturation. Results: Psychological stress by 95 dB/4 hours/day noisy exposure for 5 days significantly increased serum cortisol levels in experimental group (p=0.000) and HSP70 expression (p=0.000). The effect of Increased cortisol levels and HSP70 expression significantly decrease in MPF expression (p=0.000). Conclusion: The study concluded that psychological stress could be seen by increasing cortisol and HSP70 expression affected to decreasing MPF expression intrafollicular